Preparation method of plugging agent for shale and coal rock and water-based drilling fluid
By using high-temperature anti-nanopolymer emulsion and silane-modified nanomontmorillonite in sealing agents for shale and coal rock, a three-dimensional sealing network structure is formed, which solves the problem of poor stability of existing sealing agents at high temperatures, and achieves efficient sealing of tiny cracks of shale and coal rock and improves the overall performance of drilling fluid.
Patent Information
- Application Number
- CN202510337853.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing sealant has poor sealing effect on tiny cracks of shale and coal rock, and cannot effectively prevent the invasion of drilling fluid filtrate. It has poor stability in high temperature environments, affecting the overall performance of drilling fluid.
Using a method of preparing a sealant for shale and coal rock, a three-dimensional sealing network structure that can enter the micro-cracks of shale and coal rock are stirred and mixed by stirring and mixing the silane-modified nanomontmorillonite under specific conditions.
It has achieved efficient sealing of tiny cracks of shale and coal rock, prevented drilling fluid filtrate from invading, and maintained good sealing performance under high temperature environments, improving the safety and efficiency of drilling operations.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling fluids, and in particular to a preparation method of a plugging agent for shale and coal rock and a water-based drilling fluid. Background Art
[0002] Drilling fluid is the blood of drilling. It plays the role of cleaning the bottom of the well, carrying cuttings, balancing the formation pressure, and maintaining the stability of the well wall during drilling construction. Water-based drilling fluid is a water-based drilling fluid. Compared with traditional oil-based drilling fluid, it has irreplaceable environmental advantages and has gradually become the mainstream fluid in the drilling field.
[0003] With the large-scale development of unconventional oil and gas resources (such as shale gas and coalbed methane), the drilling process faces many challenges. Shale and coal rock have unique geological characteristics, with complex pore structures and abundant microcracks. During drilling operations, the filtrate of water-based drilling fluid can easily invade the formation through these microcracks, causing hydration expansion, dispersion and collapse of shale and coal rock, which in turn causes problems such as well wall instability, seriously affecting drilling efficiency, increasing mining costs, and may cause permanent damage to the reservoir. However, the existing plugging agents have poor plugging effects on tiny cracks and cannot effectively prevent filtrate invasion. In addition, they have poor stability in high temperature environments, and their plugging performance is greatly reduced, affecting the overall performance of the drilling fluid.
[0004] Therefore, developing a preparation method of a plugging agent for shale and coal rock and a water-based drilling fluid that can function stably at high temperatures and has high efficiency in plugging microcracks in shale and coal rock is of great significance for improving the safety and efficiency of drilling operations. Summary of the invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a method for preparing a plugging agent for shale and coal rock and a water-based drilling fluid, which solves the problem that the existing plugging agents have poor plugging effect on tiny cracks in shale and coal rock, cannot effectively prevent filtrate invasion, have poor stability in high temperature environment, and significantly reduce the plugging performance, thus affecting the overall performance of the drilling fluid.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a plugging agent for shale and coal rock comprises the following steps: Step 1: Weigh 10 parts of high temperature resistant nano polymer emulsion, 0.5-3.5 parts of silane modified nano montmorillonite and 0.5-2.0 parts of emulsifier according to weight, and set aside; the emulsifier is one of sodium lauryl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate and fatty alcohol polyoxyethylene ether; Step 2: stirring and mixing the high temperature resistant nano polymer emulsion, silane modified nano montmorillonite and emulsifier at a temperature of 25° C. and a stirring rate of 12000 r / min for 60 minutes to obtain a plugging agent for shale and coal rock; Wherein, the high temperature resistant nano polymer emulsion is prepared by the following steps: Step a1: 2-methoxy-4-vinylphenol, epichlorohydrin and tetrabutylammonium bromide are added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 10-20 min, and then the temperature is raised to 95-100° C. and the stirring reaction is continued for 4-5 h. After the reaction is completed, the reaction product is distilled under reduced pressure to remove unreacted epichlorohydrin, and then cooled to room temperature to obtain intermediate 1; Step a2: Add intermediate 1, ethylenediamine and isopropanol into a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adjust the pH to 8-9 with sodium hydroxide solution, then heat to reflux and continue stirring and reacting for 20-30 hours, after the reaction is completed, cool the reaction product to room temperature, and then remove the solvent by rotary evaporation to obtain intermediate 2; Step a3: adding intermediate 2 and anhydrous methanol to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, stirring the reaction for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then adding 1,3-propane sultone solution dropwise while stirring, controlling the dropping rate to 1-2 drops / s, and heating to 65-70° C. after the dropwise addition is completed, and stirring and reacting for 30-40 hours, and then adjusting the pH to 8-8.5 with sodium hydroxide solution, and then continuing to stir and react for 5-10 minutes. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then added to anhydrous ether, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene sulfonate monomer; Step a4: adding diene sulfonate monomer, N,N-dimethylacrylamide, acrylic acid, sodium dodecyl sulfate and deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introducing nitrogen protection, stirring and reacting for 15-25 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then adding ammonium persulfate and heating to 70-75° C. and continuing to stir and react for 6-8 hours. After the reaction is completed, the reaction product is cooled to room temperature to obtain a high temperature resistant nano polymer emulsion; Wherein, the silane-modified nano-montmorillonite is prepared by the following steps: Step b1: adding montmorillonite and deionized water to a three-necked flask equipped with a stirrer and a thermometer, stirring the mixture at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 5-6 hours, then ultrasonically treating the mixture at an ultrasonic power of 400-500 W for 20-30 minutes, then adding octadecyltrimethylammonium bromide and stirring the mixture at a temperature of 55-60° C. for 4-5 hours, cooling the reaction product to room temperature after the reaction, then centrifuging it, washing the precipitate with anhydrous ethanol and distilled water for 3-5 times in sequence, then placing it in a vacuum drying oven, and drying it at a temperature of 40-45° C. for 2-3 hours to obtain nano-modified montmorillonite; Step b2: Add the nano-modified montmorillonite and ethanol solution into a three-necked flask equipped with a stirrer, a thermometer and an air-conducting reflux condenser, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then add γ-glycidyloxypropyltrimethoxysilane and continue stirring and reacting for 10-15 hours at a temperature of 55-60°C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous ethanol for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 80-85°C for 6-7 hours to obtain silane-modified nano-montmorillonite.
[0007] As a further solution of the present invention: the usage ratio of the 2-methoxy-4-vinylphenol, epichlorohydrin and tetrabutylammonium bromide in step a1 is 10g:40-50g:1.2-1.8g.
[0008] As a further solution of the present invention: the usage ratio of the intermediate 1, ethylenediamine and isopropanol in step a2 is 10 mmol: 21-23 mmol: 60-70 mL.
[0009] As a further solution of the present invention: the mass fraction of the sodium hydroxide solution in step a2 is 15-25%.
[0010] As a further solution of the present invention: the usage ratio of the intermediate 2, anhydrous methanol and 1,3-propane sultone solution in step a3 is 10 mmol:40-50 mL:35-40 mL.
[0011] As a further solution of the present invention: the 1,3-propane sultone solution in step a3 is a solution formed by dissolving 1,3-propane sultone in anhydrous methanol at a ratio of 10 mmol:15 mL; the mass fraction of the sodium hydroxide solution is 15-25%.
[0012] As a further solution of the present invention: the usage ratio of the diene sulfonate monomer, N,N-dimethylacrylamide, acrylic acid, sodium dodecyl sulfate, deionized water and ammonium persulfate in step a4 is 8-10g:3-4g:2-3g:0.6-1.0g:70-80mL:0.1-0.3g.
[0013] As a further solution of the present invention: the usage ratio of the montmorillonite, deionized water and octadecyltrimethylammonium bromide in step b1 is 2g:70-80mL:0.1-0.2g.
[0014] As a further solution of the present invention: the usage ratio of the nano-modified montmorillonite, ethanol solution and γ-glycidyloxypropyltrimethoxysilane in step b2 is 1 g: 50-60 mL: 1.5-5.5 mL.
[0015] As a further solution of the present invention: the volume fraction of the ethanol solution in step b2 is 85-90%.
[0016] As a further solution of the present invention: a water-based drilling fluid comprises the following raw materials: Base slurry, PAC-LV viscosity enhancer, JHJS-150 fluid loss reducer, JNJS-220 high temperature resistant fluid loss reducer, JXA-1 inhibitor, plugging agent for shale and coal rock, sodium hydroxide, quicklime, RH-220 lubricant, potassium chloride, barite powder and clean water.
[0017] As a further solution of the present invention: the method for preparing the water-based drilling fluid comprises the following steps: Step 1, prepare base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30 minutes at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30 minutes, and then let it stand for 24 hours to obtain base slurry; Step 2: Prepare drilling fluid: Step S21: adding 120 g of the base slurry into 233 mL of clean water, and stirring and mixing for 5 min at a temperature of 25° C. and a stirring rate of 12000 r / min to obtain a mixed slurry; Step S22: Add 0.6g PAC-LV viscosity enhancer to the mixed slurry, and stir and mix for 5 minutes at a temperature of 25°C and a stirring rate of 4000r / min, then add 6g JHJS-150 fluid loss reducer and continue to stir and mix for 5 minutes, then add 3g JNJS-220 high temperature resistant fluid loss reducer and continue to stir and mix for 5 minutes, then add 1g JXA-1 inhibitor and continue to stir and mix for 5 minutes, then add 1g shale and coal rock plugging agent and continue to stir and mix for 5 minutes, then add 0.2g sodium hydroxide and 7g potassium chloride and continue to stir and mix for 5 minutes, then add 0.5g quicklime and continue to stir and mix for 5 minutes, then add 3.5g RH-220 lubricant and continue to stir and mix for 5 minutes, then add barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0018] Beneficial effects of the present invention: The invention discloses a method for preparing a plugging agent for shale and coal rock and a water-based drilling fluid, wherein base slurry, PAC-LV viscosity enhancer, JHJS-150 fluid loss reducer, JNJS-220 high temperature resistant fluid loss reducer, JXA-1 inhibitor, plugging agent for shale and coal rock, sodium hydroxide, quicklime, RH-220 lubricant, potassium chloride, barite powder and clean water are stirred and mixed to obtain a water-based drilling fluid; the water-based drilling fluid uses water as a continuous phase, is more environmentally friendly than oil-based drilling fluid, has a lower cost, meets the requirements of green mining and economic benefits, and adds shale and coal rock into the water-based drilling fluid; After the rock plugging agent is used, the synergistic effect of high-temperature resistant nano-polymer emulsion and silane-modified nano-montmorillonite can enter the tiny cracks of shale and coal rock and interweave with each other to jointly build a three-dimensional plugging network structure, and effectively plug the cracks, effectively preventing the drilling fluid filtrate from invading the formation. It also has excellent high-temperature resistance, which makes its structure stable under high-temperature environment, and enables it to maintain good plugging performance under harsh conditions such as high temperature, high pressure and drilling fluid flushing, meeting the high-temperature drilling needs of deep shale gas and coalbed methane extraction, and helping to improve the safety and efficiency of drilling operations.
[0019] In the process of preparing the plugging agent for shale and coal rock, a high temperature resistant nano polymer emulsion is first prepared. First, 2-methoxy-4-vinylphenol and epichlorohydrin are reacted, and the hydroxyl group on the 2-methoxy-4-vinylphenol reacts with epichlorohydrin to undergo a ring-opening reaction, and then a chlorine atom is introduced to obtain an intermediate 1. Then, the intermediate 1 reacts with ethylenediamine, and the chlorine atom on the intermediate 1 reacts with the amino group on the ethylenediamine to introduce an -NH- bond and simultaneously form two alkenyl groups to obtain an intermediate 2. Then, the intermediate 2 reacts with 1,3-propane sultone, and the -NH- on the intermediate 2 reacts with 1,3-propane sultone to undergo a ring-opening reaction to form a sodium sulfonate group to obtain a diene sulfonate monomer. Finally, the diene sulfonate monomer and N,N- Dimethylacrylamide and acrylic acid are polymerized to form a polymer to obtain a high-temperature resistant nano-polymer emulsion; the molecular structure of the high-temperature resistant nano-polymer emulsion contains a large number of benzene rings and sodium sulfonate groups, which give it high-temperature stability, and utilizes the two olefin groups on the diene sulfonate monomer to improve the cross-linking degree of the polymer, and the presence of the sodium sulfonate group and the carboxylic acid group enhances the electrostatic adsorption of the polymer microspheres. Therefore, after the high-temperature resistant nano-polymer emulsion is added to the drilling fluid, it can easily enter the micro-cracks of shale and coal rock, and utilize the active groups to undergo physical adsorption and chemical action with the crack surface, tightly adhere to the crack wall, and accumulate and fill in the crack to form an effective blockage, thereby preventing the drilling fluid filtrate from further invading the formation, thereby playing a role in plugging the micro-cracks.
[0020] In the process of preparing the plugging agent for shale and coal rock, a silane-modified nano-montmorillonite is also prepared. First, ultrasonic treatment is used to realize the exfoliation of montmorillonite, and the particle size is reduced to prepare a nano-modified montmorillonite with a layered structure. Then, γ-glycidyloxypropyltrimethoxysilane is used to treat the nano-modified montmorillonite. The siloxane on the γ-glycidyloxypropyltrimethoxysilane is hydrolyzed to form silanol, which can be effectively grafted to the surface of the nano-modified montmorillonite. At the same time, a large number of epoxy groups are introduced to obtain the silane-modified nano-montmorillonite. After the modification, the silane-modified nano-montmorillonite not only changes the surface properties of the montmorillonite, but also changes its The hydrophilicity becomes partial lipophilicity, which reduces the interaction with water and inhibits the hydration expansion of montmorillonite. In addition, the silicone group forms a certain steric hindrance on its surface, which enhances the structural stability of montmorillonite. After entering the micro-crack surface of shale and coal rock, it can be oriented on the crack surface to form a dense and flexible plugging film, which can effectively block the penetration of drilling fluid filtrate. At the same time, the epoxy group and silicone group are connected to the crack surface in the form of chemical bonds, which enhances the adhesion between montmorillonite and the crack surface, making the plugging film more solid and not easily washed away by the filtrate, further improving the plugging effect. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Embodiment 1: This embodiment is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1: 10 g of 2-methoxy-4-vinylphenol, 40 g of epichlorohydrin and 1.2 g of tetrabutylammonium bromide were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 300 r / min for 10 min, and then the temperature was raised to 95° C. and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was distilled under reduced pressure to remove unreacted epichlorohydrin, and then cooled to room temperature to obtain intermediate 1; Step S2: 10 mmol of intermediate 1, 21 mmol of ethylenediamine and 60 mL of isopropanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the pH was adjusted to 8 with a 15% mass fraction sodium hydroxide solution. The mixture was then heated to reflux and continued to stir for reaction for 20 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 2; Step S3: 10 mmol of intermediate 2 and 40 mL of anhydrous methanol are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then 35 mL of 1,3-propane sultone solution formed by dissolving 10 mmol:15 mL of 1,3-propane sultone in anhydrous methanol is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the mixture is heated to 65° C. and the stirring reaction is continued for 30 h, and then the pH is adjusted to 8 with a sodium hydroxide solution having a mass fraction of 15%, and then the stirring reaction is continued for 5 min. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then the mixture is added to anhydrous ether, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene sulfonate monomer; Step S4: 8 g of diene sulfonate monomer, 3 g of N,N-dimethylacrylamide, 2 g of acrylic acid, 0.6 g of sodium dodecyl sulfate and 70 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 15 min, and then 0.1 g of ammonium persulfate was added and the mixture was heated to 70° C. and stirred for reaction for 6 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a high temperature resistant nano polymer emulsion; Step S5: 2 g of montmorillonite and 70 mL of deionized water are added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 5 h, and then ultrasonically treated for 20 min at an ultrasonic power of 400 W, and then 0.1 g of octadecyltrimethylammonium bromide is added and the mixture is stirred for reaction for 4 h at a temperature of 55° C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged, and the precipitate is washed three times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 40° C. for 2 h to obtain nano-modified montmorillonite; Step S6: 1 g of nano-modified montmorillonite and 50 mL of an ethanol solution with a volume fraction of 85% are added to a three-necked flask equipped with a stirrer, a thermometer, and a gas-conducting reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then 1.5 mL of γ-glycidyloxypropyltrimethoxysilane is added and the mixture is heated to 55° C. and the stirring reaction is continued for 10 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 80° C. for 6 h to obtain silane-modified nano-montmorillonite; Step S7: 10 parts of high temperature resistant nano polymer emulsion, 0.5 parts of silane modified nano montmorillonite and 0.5 parts of emulsifier are weighed in parts by weight for later use; the emulsifier is sodium dodecyl sulfate; Step S8: stirring and mixing the high temperature resistant nano polymer emulsion, the silane modified nano montmorillonite and the emulsifier at a temperature of 25° C. and a stirring rate of 12000 r / min for 60 minutes to obtain a plugging agent for shale and coal rock; Step S9, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30 minutes at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30 minutes, and then stand for 24 hours to obtain base slurry; Step S10, preparing drilling fluid: adding 120g of base slurry to 233mL of clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g of PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g of JHJS-150 fluid loss reducer and continuing to stir and mix for 5min, and then adding 3g of JNJS -220 high temperature resistant fluid loss reducer, continue to stir and mix for 5 minutes, then add 1g JXA-1 inhibitor, continue to stir and mix for 5 minutes, then add 1g shale and coal rock plugging agent, continue to stir and mix for 5 minutes, then add 0.2g sodium hydroxide and 7g potassium chloride, continue to stir and mix for 5 minutes, then add 0.5g quicklime, continue to stir and mix for 5 minutes, then add 3.5g RH-220 lubricant, continue to stir and mix for 5 minutes, then add barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0023] Embodiment 2: This embodiment is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1: 10 g of 2-methoxy-4-vinylphenol, 45 g of epichlorohydrin and 1.5 g of tetrabutylammonium bromide were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 15 min, and then the temperature was raised to 98° C. and the stirring reaction was continued for 4.5 h. After the reaction was completed, the reaction product was distilled under reduced pressure to remove unreacted epichlorohydrin, and then cooled to room temperature to obtain intermediate 1; Step S2: 10 mmol of intermediate 1, 22 mmol of ethylenediamine and 65 mL of isopropanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the pH was adjusted to 8.5 with a 20% mass fraction sodium hydroxide solution. The mixture was then heated to reflux and continued to stir for reaction for 25 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 2; Step S3: 10 mmol of intermediate 2 and 45 mL of anhydrous methanol were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then 38 mL of 1,3-propane sultone solution formed by dissolving 10 mmol:15 mL of 1,3-propane sultone in anhydrous methanol was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the mixture was heated to 68° C. and continued to stir for reaction for 35 h, and then adjusted to pH 8 with a sodium hydroxide solution having a mass fraction of 20%, and then continued to stir for reaction for 8 min. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation, and then added to anhydrous ether, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain a diene sulfonate monomer; Step S4: 9 g of diene sulfonate monomer, 3.5 g of N,N-dimethylacrylamide, 2.5 g of acrylic acid, 0.8 g of sodium dodecyl sulfate and 75 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 20 min, and then 0.2 g of ammonium persulfate was added and the mixture was heated to 72° C. and stirred for reaction for 7 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a high temperature resistant nano polymer emulsion; Step S5: 2 g of montmorillonite and 75 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 5.5 h, and then ultrasonically treated for 25 min at an ultrasonic power of 450 W, and then 0.15 g of octadecyltrimethylammonium bromide was added and the mixture was stirred for reaction at a temperature of 58° C. for 4.5 h. After the reaction, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed with anhydrous ethanol and distilled water for 4 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 42° C. for 2.5 h to obtain nano-modified montmorillonite; Step S6: 1 g of nano-modified montmorillonite and 55 mL of an ethanol solution with a volume fraction of 88% are added to a three-necked flask equipped with a stirrer, a thermometer, and a gas-conducting reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then 3.5 mL of γ-glycidyloxypropyltrimethoxysilane is added and the mixture is heated to 58° C. and stirred for reaction for 12 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with anhydrous ethanol for 4 times, and then placed in a vacuum drying oven and dried at a temperature of 82° C. for 6.5 h to obtain silane-modified nano-montmorillonite; Step S7: weigh 10 parts of high temperature resistant nano polymer emulsion, 2 parts of silane modified nano montmorillonite and 1.2 parts of emulsifier according to weight, and set aside; the emulsifier is sodium fatty alcohol polyoxyethylene ether sulfate; Step S8: stirring and mixing the high temperature resistant nano polymer emulsion, the silane modified nano montmorillonite and the emulsifier at a temperature of 25° C. and a stirring rate of 12000 r / min for 60 minutes to obtain a plugging agent for shale and coal rock; Step S9, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30 minutes at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30 minutes, and then stand for 24 hours to obtain base slurry; Step S10, preparing drilling fluid: adding 120g of base slurry to 233mL of clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g of PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g of JHJS-150 fluid loss reducer and continuing to stir and mix for 5min, and then adding 3g of JNJS -220 high temperature resistant fluid loss reducer, continue to stir and mix for 5 minutes, then add 1g JXA-1 inhibitor, continue to stir and mix for 5 minutes, then add 1g shale and coal rock plugging agent, continue to stir and mix for 5 minutes, then add 0.2g sodium hydroxide and 7g potassium chloride, continue to stir and mix for 5 minutes, then add 0.5g quicklime, continue to stir and mix for 5 minutes, then add 3.5g RH-220 lubricant, continue to stir and mix for 5 minutes, then add barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0024] Embodiment 3: This embodiment is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1: 10 g of 2-methoxy-4-vinylphenol, 50 g of epichlorohydrin and 1.8 g of tetrabutylammonium bromide were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 20 min, and then the temperature was raised to 100° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was distilled under reduced pressure to remove unreacted epichlorohydrin, and then cooled to room temperature to obtain intermediate 1; Step S2: 10 mmol of intermediate 1, 23 mmol of ethylenediamine and 70 mL of isopropanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the pH was adjusted to 9 with a 25% sodium hydroxide solution. The mixture was then heated to reflux and stirred for reaction for 30 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 2; Step S3: 10 mmol of intermediate 2 and 50 mL of anhydrous methanol are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 40 mL of 1,3-propane sultone solution formed by dissolving 10 mmol:15 mL of 1,3-propane sultone in anhydrous methanol is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the mixture is heated to 70° C. and the stirring reaction is continued for 40 h, and then the pH is adjusted to 8.5 with a sodium hydroxide solution having a mass fraction of 25%, and then the stirring reaction is continued for 10 min. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then the mixture is added to anhydrous ether, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene sulfonate monomer; Step S4: 10 g of diene sulfonate monomer, 4 g of N,N-dimethylacrylamide, 3 g of acrylic acid, 1.0 g of sodium dodecyl sulfate and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 25 min, and then 0.3 g of ammonium persulfate was added and the mixture was heated to 75° C. and stirred for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a high temperature resistant nano polymer emulsion; Step S5: 2 g of montmorillonite and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred at 30° C. and 400 r / min for 6 h, and then ultrasonically treated at an ultrasonic power of 500 W for 30 min, and then 0.2 g of octadecyltrimethylammonium bromide was added and the mixture was stirred at 60° C. for 5 h. After the reaction, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with anhydrous ethanol and distilled water for 5 times in sequence, and then placed in a vacuum drying oven and dried at 45° C. for 3 h to obtain nano-modified montmorillonite; Step S6: 1 g of nano-modified montmorillonite and 60 mL of 90% ethanol solution by volume were added to a three-necked flask equipped with a stirrer, a thermometer and a gas-conducting reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 30° C. and a stirring rate of 400 r / min for 30 min, and then 5.5 mL of γ-glycidyloxypropyltrimethoxysilane was added and the mixture was heated to 60° C. and stirred for reaction for 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at 85° C. for 7 h to obtain silane-modified nano-montmorillonite. Step S7: 10 parts of high temperature resistant nano polymer emulsion, 3.5 parts of silane modified nano montmorillonite and 2.0 parts of emulsifier are weighed in parts by weight for later use; the emulsifier is fatty alcohol polyoxyethylene ether; Step S8: stirring and mixing the high temperature resistant nano polymer emulsion, the silane modified nano montmorillonite and the emulsifier at a temperature of 25° C. and a stirring rate of 12000 r / min for 60 minutes to obtain a plugging agent for shale and coal rock; Step S9, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30 minutes at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30 minutes, and then stand for 24 hours to obtain base slurry; Step S10, preparing drilling fluid: adding 120g of base slurry to 233mL of clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g of PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g of JHJS-150 fluid loss reducer and continuing to stir and mix for 5min, and then adding 3g of JNJS -220 high temperature resistant fluid loss reducer, continue to stir and mix for 5 minutes, then add 1g JXA-1 inhibitor, continue to stir and mix for 5 minutes, then add 1g shale and coal rock plugging agent, continue to stir and mix for 5 minutes, then add 0.2g sodium hydroxide and 7g potassium chloride, continue to stir and mix for 5 minutes, then add 0.5g quicklime, continue to stir and mix for 5 minutes, then add 3.5g RH-220 lubricant, continue to stir and mix for 5 minutes, then add barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0025] Comparative Example 1: This comparative example is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1: 4 g of N,N-dimethylacrylamide, 3 g of acrylic acid, 1.0 g of sodium dodecyl sulfate and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 25 min, and then 0.3 g of ammonium persulfate was added and the mixture was heated to 75° C. and stirred for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a nanopolymer emulsion; Step S2, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30min at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30min, and then stand for 24h to obtain base slurry; Step S3, preparing drilling fluid: adding 120g base slurry to 233mL clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g JHJS-150 filtrate reducer and continuing to stir and mix for 5min, then adding 3g JNJS-220 high temperature resistant filtrate reducer and continuing to stir and mix for 5min, then adding 1g JXA-1 inhibitor and continuing to stir and mix for 5min, then adding 1g nano polymer emulsion and continuing to stir and mix for 5min, then adding 0.2g sodium hydroxide and 7g potassium chloride and continuing to stir and mix for 5min, then adding 0.5g quicklime and continuing to stir and mix for 5min, then adding 3.5g RH-220 lubricant and continuing to stir and mix for 5min, then adding barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0026] Comparative Example 2: This comparative example is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1: 10 g of 2-methoxy-4-vinylphenol, 50 g of epichlorohydrin and 1.8 g of tetrabutylammonium bromide were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 20 min, and then the temperature was raised to 100° C. and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was distilled under reduced pressure to remove unreacted epichlorohydrin, and then cooled to room temperature to obtain intermediate 1; Step S2: 10 mmol of intermediate 1, 23 mmol of ethylenediamine and 70 mL of isopropanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the pH was adjusted to 9 with a 25% sodium hydroxide solution. The mixture was then heated to reflux and stirred for reaction for 30 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 2; Step S3: 10 mmol of intermediate 2 and 50 mL of anhydrous methanol are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 40 mL of 1,3-propane sultone solution formed by dissolving 10 mmol:15 mL of 1,3-propane sultone in anhydrous methanol is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the mixture is heated to 70° C. and the stirring reaction is continued for 40 h, and then the pH is adjusted to 8.5 with a sodium hydroxide solution having a mass fraction of 25%, and then the stirring reaction is continued for 10 min. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then the mixture is added to anhydrous ether, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a diene sulfonate monomer; Step S4: 10 g of diene sulfonate monomer, 4 g of N,N-dimethylacrylamide, 3 g of acrylic acid, 1.0 g of sodium dodecyl sulfate and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 25 min, and then 0.3 g of ammonium persulfate was added and the mixture was heated to 75° C. and stirred for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a high temperature resistant nano polymer emulsion; Step S5, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30min at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30min, and then stand for 24h to obtain base slurry; Step S6, preparing drilling fluid: adding 120g base slurry to 233mL clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g JHJS-150 fluid loss reducer and continuing to stir and mix for 5min, then adding 3g JNJS-220 high temperature resistant fluid loss reducer and continuing to stir and mix for 5min, then adding 1g JXA-1 inhibitor and continuing to stir and mix for 5min, then adding 1g high temperature resistant nano polymer emulsion and continuing to stir and mix for 5min, then adding 0.2g sodium hydroxide and 7g potassium chloride and continuing to stir and mix for 5min, then adding 0.5g quicklime and continuing to stir and mix for 5min, then adding 3.5g RH-220 lubricant and continuing to stir and mix for 5min, then adding barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0027] Comparative Example 3: This comparative example is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1: 2 g of montmorillonite and 80 mL of deionized water are added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 6 h, and then ultrasonically treated for 30 min at an ultrasonic power of 500 W, and then 0.2 g of octadecyltrimethylammonium bromide is added and the mixture is stirred for reaction for 5 h at a temperature of 60° C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged, and the precipitate is washed 5 times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 45° C. for 3 h to obtain nano-modified montmorillonite; Step S2: 1 g of nano-modified montmorillonite and 60 mL of 90% ethanol solution by volume were added to a three-necked flask equipped with a stirrer, a thermometer and a gas-conducting reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then 5.5 mL of γ-glycidyloxypropyltrimethoxysilane was added and the temperature was raised to 60° C. and the stirring reaction was continued for 15 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with anhydrous ethanol for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 7 h to obtain silane-modified nano-montmorillonite; Step S3, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30min at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30min, and then stand for 24h to obtain base slurry; Step S4, preparing drilling fluid: adding 120g of base slurry to 233mL of clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g of PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g of JHJS-150 filtrate reducer and continuing to stir and mix for 5min, and then adding 3g of JNJS -220 high temperature resistant fluid loss reducer was stirred and mixed for 5 minutes, then 1g JXA-1 inhibitor was added and stirred and mixed for 5 minutes, then 1g silane modified nano-montmorillonite was added and stirred and mixed for 5 minutes, then 0.2g sodium hydroxide and 7g potassium chloride were added and stirred and mixed for 5 minutes, then 0.5g quicklime was added and stirred and mixed for 5 minutes, then 3.5g RH-220 lubricant was added and stirred and mixed for 5 minutes, then barite powder was added to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0028] Comparative Example 4: This comparative example is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1: 4 g of N,N-dimethylacrylamide, 3 g of acrylic acid, 1.0 g of sodium dodecyl sulfate and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 25 min, and then 0.3 g of ammonium persulfate was added and the mixture was heated to 75° C. and stirred for 8 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain a nanopolymer emulsion; Step S2: 2 g of montmorillonite and 80 mL of deionized water are added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 6 h, and then ultrasonically treated for 30 min at an ultrasonic power of 500 W, and then 0.2 g of octadecyltrimethylammonium bromide is added and the mixture is stirred for reaction for 5 h at a temperature of 60° C. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged, and the precipitate is washed 5 times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 45° C. for 3 h to obtain nano-modified montmorillonite; Step S3: weighing 10 parts of nano polymer emulsion, 3.5 parts of nano modified montmorillonite and 2.0 parts of emulsifier according to weight for later use; the emulsifier is fatty alcohol polyoxyethylene ether; Step S4: stirring and mixing the nano polymer emulsion, nano modified montmorillonite and emulsifier at a temperature of 25° C. and a stirring rate of 12000 r / min for 60 min to obtain a plugging agent for shale and coal rock; Step S5, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30min at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30min, and then stand for 24h to obtain base slurry; Step S6, preparing drilling fluid: adding 120g of base slurry to 233mL of clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g of PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g of JHJS-150 fluid loss reducer and continuing to stir and mix for 5min, and then adding 3g of JNJS -220 high temperature resistant fluid loss reducer, continue to stir and mix for 5 minutes, then add 1g JXA-1 inhibitor, continue to stir and mix for 5 minutes, then add 1g shale and coal rock plugging agent, continue to stir and mix for 5 minutes, then add 0.2g sodium hydroxide and 7g potassium chloride, continue to stir and mix for 5 minutes, then add 0.5g quicklime, continue to stir and mix for 5 minutes, then add 3.5g RH-220 lubricant, continue to stir and mix for 5 minutes, then add barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0029] Comparative Example 5: This comparative example is a method for preparing a water-based drilling fluid, comprising the following steps: Step S1, preparing base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30min at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30min, and then stand for 24h to obtain base slurry; Step S2, preparing drilling fluid: adding 120g base slurry to 233mL clean water, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 12000r / min to obtain a mixed slurry; adding 0.6g PAC-LV tackifier to the mixed slurry, and stirring and mixing for 5min at a temperature of 25°C and a stirring rate of 4000r / min, then adding 6g JHJS-150 filtrate reducer and continuing to stir and mix for 5min, then adding 3g JNJS-220 high temperature resistant filtrate reducer and continuing to stir and mix for 5min, then adding 1g JXA-1 inhibitor and continuing to stir and mix for 5min, then adding 0.2g sodium hydroxide and 7g potassium chloride and continuing to stir and mix for 5min, then adding 0.5g quicklime and continuing to stir and mix for 5min, then adding 3.5g RH-220 lubricant and continuing to stir and mix for 5min, then adding barite powder to increase the density to 1.8g / cm 3, and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
[0030] The performance of the water-based drilling fluids of Examples 1-3 and Comparative Examples 1-5 was tested, and the test results are shown in the following table:
[0031] Referring to the data in the above table, according to the comparison between Examples 1-3 and Comparative Examples 1-5, it can be seen that the water-based drilling fluid of the present invention has excellent plugging performance, and its rheological properties do not change much after high-temperature hot rolling aging, indicating that it has excellent high temperature resistance, a cuttings rolling recovery rate of more than 95%, and excellent inhibition performance.
[0032] The rheological properties were evaluated by measuring the apparent viscosity and plastic viscosity before and after 150°C hot rolling aging for 16 hours at 50°C.
[0033] The plugging performance evaluation method is as follows: using a 220nm pore size filter membrane to test the high temperature and high pressure (180℃ / 3.5MPa) filtration loss of the water-based drilling fluid after 16h of high temperature hot rolling aging at 180℃; Among them, the inhibition performance evaluation method is as follows: wherein, the shale recovery rate is to use 10g of 6-10 mesh dry shale and coal rock cuttings, mix them evenly, and soak them in 350mL of deionized water, water-based drilling fluid of Examples 1-3 and Comparative Examples 1-5 respectively, after high-temperature aging at 150°C for 16h, filter the aged cuttings with a 40-mesh sieve and dehydrate them in a vacuum drying oven at 110°C for 4h, weigh the dried cuttings, and calculate the cuttings recovery rate (cuttings recovery rate = remaining cuttings mass / initial cuttings mass × 100%), so as to evaluate the inhibition performance of shale and coal rock cuttings fluids.
[0034] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0035] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a plugging agent for shale and coal rock, characterized in that: The following steps are involved: Step 1: Weigh 10 parts of high temperature resistant nano polymer emulsion, 0.5-3.5 parts of silane modified nano montmorillonite and 0.5-2.0 parts of emulsifier according to weight, and set aside; the emulsifier is one of sodium lauryl sulfate, sodium fatty alcohol polyoxyethylene ether sulfate and fatty alcohol polyoxyethylene ether; Step 2: stirring and mixing the high temperature resistant nano polymer emulsion, silane modified nano montmorillonite and emulsifier at a temperature of 25° C. and a stirring rate of 12000 r / min for 60 minutes to obtain a plugging agent for shale and coal rock; Wherein, the high temperature resistant nano polymer emulsion is prepared by the following steps: Step a1: 2-methoxy-4-vinylphenol, epichlorohydrin and tetrabutylammonium bromide are stirred for reaction, and after the reaction is completed, the reaction product is distilled under reduced pressure to obtain intermediate 1; Step a2: stirring the intermediate 1, ethylenediamine and isopropanol for reaction, then adjusting the pH with a sodium hydroxide solution, and then continuing the stirring reaction. After the reaction is completed, the reaction product is cooled and then rotary evaporated to obtain the intermediate 2; Step a3: Stir the intermediate 2 and anhydrous methanol for reaction, then add 1,3-propane sultone solution dropwise while stirring, continue stirring the reaction after the dropwise addition is completed, then adjust the pH with sodium hydroxide solution, then continue stirring the reaction, after the reaction is completed, cool the reaction product, then rotary evaporate, then add it to anhydrous ether, then vacuum filter, and rotary evaporate the filtrate to obtain a diene sulfonate monomer; Step a4: stirring the diene sulfonate monomer, N,N-dimethylacrylamide, acrylic acid, sodium dodecyl sulfate and deionized water for reaction, then adding ammonium persulfate and continuing the stirring reaction, and cooling the reaction product after the reaction is completed to obtain a high temperature resistant nano polymer emulsion.
2. The method for preparing a plugging agent for shale and coal rock according to claim 1, characterized in that: in, The silane-modified nano-montmorillonite is prepared by the following steps: Step b1: stirring montmorillonite and deionized water for reaction, then ultrasonic treatment, then adding octadecyltrimethylammonium bromide for reaction, cooling the reaction product after the reaction, then centrifuging, washing and drying the precipitate to obtain nano-modified montmorillonite; Step b2: stirring the nano-modified montmorillonite and ethanol solution to react, then adding γ-glycidyloxypropyltrimethoxysilane and continuing to stir the reaction, cooling the reaction product after the reaction is completed, then centrifuging, washing and drying the precipitate to obtain silane-modified nano-montmorillonite.
3. The method for preparing a plugging agent for shale and coal rock according to claim 1, characterized in that: The usage ratio of the 2-methoxy-4-vinylphenol, epichlorohydrin and tetrabutylammonium bromide in step a1 is 10g:40-50g:1.2-1.8g.
4. The method for preparing a plugging agent for shale and coal rock according to claim 1, characterized in that: The usage ratio of the intermediate 1, ethylenediamine and isopropanol in step a2 is 10mmol:21-23mmol:60-70mL; the mass fraction of the sodium hydroxide solution is 15-25%.
5. The method for preparing a plugging agent for shale and coal rock according to claim 1, characterized in that: The amount ratio of the intermediate 2, anhydrous methanol and 1,3-propane sultone solution in step a3 is 10mmol:40-50mL:35-40mL; the 1,3-propane sultone solution is a solution formed by dissolving 1,3-propane sultone in anhydrous methanol at a ratio of 10mmol:15mL; the mass fraction of the sodium hydroxide solution is 15-25%.
6. The method for preparing a plugging agent for shale and coal rock according to claim 1, characterized in that: The usage ratio of the diene sulfonate monomer, N,N-dimethylacrylamide, acrylic acid, sodium dodecyl sulfate, deionized water and ammonium persulfate in step a4 is 8-10g:3-4g:2-3g:0.6-1.0g:70-80mL:0.1-0.3g.
7. The method for preparing a plugging agent for shale and coal rock according to claim 1, characterized in that: The usage ratio of the montmorillonite, deionized water and octadecyltrimethylammonium bromide in step b1 is 2g:70-80mL:0.1-0.2g.
8. The method for preparing a plugging agent for shale and coal rock according to claim 1, characterized in that: The usage ratio of the nano-modified montmorillonite, ethanol solution and γ-glycidyloxypropyltrimethoxysilane in step b2 is 1 g: 50-60 mL: 1.5-5.5 mL; the volume fraction of the ethanol solution is 85-90%.
9. A water-based drilling fluid, characterized in that: Including the following ingredients: Base slurry, PAC-LV viscosity enhancer, JHJS-150 fluid loss reducer, JNJS-220 high temperature resistant fluid loss reducer, JXA-1 inhibitor, plugging agent for shale and coal rock, sodium hydroxide, quicklime, RH-220 lubricant, potassium chloride, barite powder and clean water.
10. A method for preparing a water-based drilling fluid as claimed in claim 9, characterized in that: The following steps are involved: Step 1, prepare base slurry: weigh clean water, raw ore soil and anhydrous sodium carbonate according to the ratio of clean water, raw ore soil and anhydrous sodium carbonate of 93.64g:6g:0.36g, then add anhydrous sodium carbonate to clean water, and stir and mix for 30 minutes at a temperature of 25°C and a stirring rate of 1000r / min, then add raw ore soil and continue stirring and reacting for 30 minutes, and then let it stand for 24 hours to obtain base slurry; Step 2: Prepare drilling fluid: Step S21: adding 120 g of the base slurry into 233 mL of clean water, and stirring and mixing for 5 min at a temperature of 25° C. and a stirring rate of 12000 r / min to obtain a mixed slurry; Step S22: Add 0.6g PAC-LV viscosity enhancer to the mixed slurry, and stir and mix for 5 minutes at a temperature of 25°C and a stirring rate of 4000r / min, then add 6g JHJS-150 fluid loss reducer and continue to stir and mix for 5 minutes, then add 3g JNJS-220 high temperature resistant fluid loss reducer and continue to stir and mix for 5 minutes, then add 1g JXA-1 inhibitor and continue to stir and mix for 5 minutes, then add 1g shale and coal rock plugging agent and continue to stir and mix for 5 minutes, then add 0.2g sodium hydroxide and 7g potassium chloride and continue to stir and mix for 5 minutes, then add 0.5g quicklime and continue to stir and mix for 5 minutes, then add 3.5g RH-220 lubricant and continue to stir and mix for 5 minutes, then add barite powder to increase the density to 1.8g / cm 3 , and then stirred and mixed for 20 minutes at a temperature of 25°C and a stirring rate of 12000 r / min to obtain drilling fluid.
Citation Information
Patent Citations
Water-based drilling fluid suitable for long-section horizontal well of shale gas and application of water-based drilling fluid
CN106833564A
Synthesis of high-temperature-resistant modified nano aluminum oxide blocking agent and oil-based drilling fluid
CN114395378A
240 DEG C-resistant salt-resistant plugging type water-based drilling fluid as well as preparation method and application thereof
CN115466603A
Dry mix for water based drilling fluid
US6818596B1
Cited By
Bonding type hyperbranched nanorod cementing wall-fixing agent as well as preparation method and application thereof
CN122060473A
A bonded hyperbranched nanorod cementing wall agent and a preparation method and application thereof
CN122060473B